Floral development and assisted pollination compatibility of D197 durian variety (raja kunyit/musang king) - Nurlisa, Su Sy Ei (2021)
Durian is a fruit under family Bombacaceae carrying the genus Durio has long been known as king of fruit and is locally highly in demand when it comes to seasonal fruits. Musang King (D197) variety is receiving a lot of attention due to its high-quality taste of arils. As the interest of growers increase for Musang King variety and to optimise its fruit production, growers start to plant durian in monovariety fashion instead as recommended conventionally to plant more than one variety in a planting area. Thus, this study aim is to elucidate the pollination compatibility status of Durio zibethinus variety D197 (Musang King) with regard of high fruit sets. Musang King trees used in this study were located at durian orchards in Lembah Klau, Raub, Pahang owned by Lembah Temir Resort. The experiment was carried out by pollinating flower of Musang King as maternal with Musang King pollen of the same tree (PST), with Musang King pollen of different tree (PDT), with pollen of D24 (xenogamy), autonomous autogamy and in comparison, with openly pollinated acted as control. Fruit sets of each treatment were recorded at 7th, 14th, 21st, 28th days after anthesis or pollination and at harvest. Musang King durian flowers showed herkogamy condition as the stamen tend to curve outward away from the stigma during anthesis and throughout the flower development there is difference of height between stigma and anther. Pollination study showed crossing of Musang King with D24 variety produce significant higher fruit set which was 16.28% at harvest while other treatments had 0% of fruits set at harvest except for control or open pollination which fruits set recorded were 0.87%. Fruits set were significantly higher when Musang King flowers were cross pollinated with D24 pollens (Xenogamy) compared to when selfpollinated and open pollination. This indicated that Musang King is suitable to be planted in polyvarieties instead of monovariety.